Study of the heat capacity of the derivatives C21H16N2O and C21H19N2O2Br of the alkaloid harmine - Kasenova, S.B.; Sagintaeva, Zh.I.; Tukhmetova, Zh.K.; Kasenov, B.K.; Nurmaganbetov, Zh.S.; Adekenov, S.M. (Springer, 2011)
Temperature dependences of the heat capacity of the alkaloid harmine derivatives 9-methoxy-2-phenyl-11H-indolysine[8,7-b]indole (С21Н16N2O) and N-(2)-phenacylharminium bromide C21H19N2O2Br were studied by the experimental calorimetry method.
Keywords: Heat Capacity; Derivatives С21Н16N2O; the Alkaloid Harmine